ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM PERCAKAPAN GRUP WHATSAPP “MX PRIDE SULAWESI” - Eril, Muhammad; safar, Muh; idris, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the types of Indonesian language errors in the MX Pride Sulawesi WhatsApp group conversation. The study used a descriptive qualitative approach with a content analysis design. The data source was text messages from group members which were analyzed based on the General Guidelines for Indonesian Spelling (PUEBI). The results showed four main categories of language errors, namely (1) letter usage, including neglecting capitalization at the beginning of sentences and entity names, the use of full capital letters for emotional emphasis, and inaccurate marking of foreign terms; (2) word spelling, including separating elements of words that should be connected, the use of abbreviations and numbers as borrowings, in the form of using foreign words without spelling adaptation or italics; and (4) use of punctuation, such as the omission of question marks, periods, or commas, excessive use of ellipsis and exclamation marks, and inaccurate use of hyphens and colons. These findings indicate that digital communication patterns tend to prioritize speed and personal expression over adherence to standard language rules. This study is expected to be a reference in the study of language errors in digital media and increase awareness of the use of Indonesian according to PUEBI rules.